SHORT COMMUNICATION: PROFITABILITY OF BEEKEEPING USING LOCALLY MADE TRANSITIONAL TOP BAR BEEHIVE IN WOLMERA WOREDA, OROMIA REGION, ETHIOPIA - Endale, Wongelu (Asian Journal of Agriculture, 2020)
Abstract. Gobena WE. 2020. Short Communication: Profitability of beekeeping using locally made transitional top bar beehive in Wolmera Woreda, Oromia Region, Ethiopia. Asian J Agric 4: 1-4. Beekeeping is an important source of livelihood and can be integrated with other agricultural activities. The objective of this study is to assess the profitability of beekeeping using locally built transitional topbar hive. Two-stage sampling procedure and stratified sampling technique used in the study. Primary and secondary data are collected analyzed using descriptive statistics and partial budgeting. The partial budgeting result reveals that beekeeping is profitable by using this hive with incremental net benefit of 462.12 ETB and the beekeepers increased their benefit from the hive by more than 2.9 fold by using this beehive as compared to traditional hive. The study concludes beekeeping with this hive can be profitable business for the marginal farmers who have little business capital and land resource. Moreover, income from a single bee colony at beekeeper?s backyard can be improved with minimum cost if this hive with its package used. The overall finding of this study mainly underlined the importance of extension support and technical back to the beekeepers to use this hive.